The effect of drainage on the quality of brook waters in the Kiiminkijoki River basin, Northern Finland - Hynninen, Pekka; Sepponen, Pentti (Silva Fennica, 1983)
The present study deals with the effect of forest drainage on some quality factors of brook waters. Under study were several brooks in the basin of the Kiiminkijoki River as well as its main tributary, the Nuorittajoki River. These are located in Northern Finland and belong to the international water program Project Aqua. The following values were determined for the water samples: pH, electric conductivity, colour, concentration of suspended solids., NO, NO, and NH nitrogen concentrations, dissolved and total phosphorus, and Ca, Mg, K and Fe concentrations. Water quality in the brooks was monitored prior to and after ditching. A statistically significant change was noted in colour, in the concentration of suspended solids, in the NH concentration and in some brooks also in the pH value and in the total phosphorus, K, and Fe concentrations.2344